Pelatihan Mengenal Karakter Dasar Siswa untuk Coaching di SMK Telkom Makassar - Indrabayu Indrabayu; Ingrid Nurtanio; Ady Wahyudi; Christoforus Yohannes; Ais Prayogi; Elly Warni; Anugrayani Bustamin; Astri Oktianawaty; A. Marimar Muchtamar; Intan Sari Areni (Faculty of Engineering UNHAS, 2021)
This rapid technological development needs to be addressed wisely regarding the millennial generation. One of them is knowing the character and mindset of the millennial generation. This community service aims to provide new insights and knowledge for teachers and specifically for students to recognize basic characters. Character education is one of the main discourses in national policies in the field of character education. The entire teaching and learning process must refer to character development and this is something that partners will implement, in this case, SMK Telkom Makassar. The implementation of community service is carried out by two methods, namely the socialization of basic character recognition and Brain Color tests. This socialization consists of introducing basic characters which is also one of the sub-topics in the Technopreneurship Course taught at the Department of Informatics Engineering, Hasanuddin University. And as a solution in solving partner problems, a brain color test is carried out to identify the personality color of each student. The results of each student's Brain Color model can be used as a reference in developing teaching and learning process strategies. This community service was attended by 63 teachers of SMK Telkom through a zoom meeting. The participants were very enthusiastic in participating in this activity, as seen from the questionnaire results, which showed 96% agreed with the implementation of the method introduced. In addition, the participants also hoped that there would be further training related to the introduction of student characters which are important in the learning process at school.